Differences in physiological responses during rowing and cycle ergometry in elite male rowers - Lindenthaler, J. R.; Rice, A. J.; Versey, N. G.; McKune, A. J.; Welvaert, M. (Frontiers in Physiology, 2018)
Cycle training is an important training modality of elite rowers. Cycling is the preferred alternative to on-water and ergometer rowing as it provides a reduction in compressive forces on the thoracic cage and upper extremities while still creating a local and central acclimation to endurance training. It is hypothesised, however, that there will be differences in physiological characteristics between Concept II (CII) rowing and WattBike (WB) cycling due to the principle regarding the specificity of training that elite rowers undertake. Understanding these differences will ensure more accurate training prescription when cycling. Twenty international level male rowers, [VO2PEAK 5.85 ± 0.58 L.min-1 (CI ± 0.26 L.min-1)] participated in two identical discontinuous incremental exercise tests on a CII rowing and WB cycle ergometer. Ergometer modalities were randomised and counterbalanced among the group and tests occurred 7 days apart. VO2, VCO2, VE(STPD) and HR were significantly higher for every submaximal power output on the CII compared with the WB. Maximal power output on the WB was higher than on the CII [42 ± 33 W (CI ± 14 W) p < 0.000] but VO2PEAK was similar between modalities. Minute ventilation at maximal exercise was 11 L.min-1 lower on CII than on WB. When data were expressed relative to modality specific VO2PEAK, power output was consistently lower on the CII as was submaximal VCO2, RER, RPE, mechanical efficiency and BLa concentration at 75% VO2PEAK. Across all power outputs and exercise modalities, 77% of the variance in RPE could be explained by the variance in BLa. These results demonstrate that elite rowers can attain similar VO2PEAK scores regardless of modality. Substantial physiological and metabolic differences are evident between CII rowing and WB cycling when power output is the independent variable with the latter being over 40 W higher. The difference in displayed power output between the ergometer modalities is attributed to differences in mechanical efficiency and a degree of power output not being accounted for on the CII ergometer. Given the lack of consistency between CII and WB power output, other physiological measures, such as HR, are better suited to prescribe WB ergometer sessions.